Versus Exclusion: The Political Dynamics Between the "National" and the "International" in Contemporary Philippine Literary History - Lumbera, Bienvenido L. (Likhaan: The Journal of Contemporary Philippine Literature; Vol 3 (2009): Likhaan 3, 2010)
No abstract yet